Impact of Intensive Glycemic Treatment on Diabetes Complications-A Systematic Review - Juliana Poonoosamy; Philippe Lopes; Priscille Huret; Randa Dardari; Alfred Penfornis; Claire Thomas; Dured Dardari (MDPI AG, 2023)
Diabetes complications can be related to the long duration of the disease or chronic hyperglycemia. The follow-up of diabetic patients is based on the control of chronic hyperglycemia, although this correction, if obtained rapidly in people living with severe chronic hyperglycemia, can paradoxically interfere with the disease or even induce complications. We reviewed the literature describing the impact of the rapid and intense treatment of hyperglycemia on diabetic complications. The literature review showed that worsening complications occurred significantly in diabetic microangiopathy with the onset of specific neuropathy induced by the correction of diabetes. The results for macroangiopathy were somewhat mixed with the intensive and rapid correction of chronic hyperglycemia having a neutral impact on stroke and myocardial infarction but a significant increase in cardiovascular mortality. The management of diabetes has now entered a new era with new therapeutic molecules, such as gliflozin for patients living with type 2 diabetes, or hybrid insulin delivery systems for patients with insulin-treated diabetes. Our manuscript provides evidence in support of these personalized and progressive algorithms for the control of chronic hyperglycemia.